2020
DOI: 10.1002/ana.25881
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation Promotes Gait Training in Parkinson Disease

Abstract: Objective: To determine whether priming with 1 or 25Hz repetitive transcranial magnetic stimulation (rTMS) will enhance the benefits from treadmill training up to 3 months postintervention in people with Parkinson disease (PD), and to evaluate the underlying changes in cortical excitability. Methods: This randomized double-blind, placebo-controlled trial was conducted between October 2016 and December 2018. Fifty-one participants with PD were randomized to receive 12 sessions of rTMS (25Hz, 1Hz, or sham) follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 58 publications
0
37
0
1
Order By: Relevance
“…Indeed, Ziemann et al [ 87 ] found that better outcomes on a thumb abduction movement training could be achieved when participants have received LTD-like plasticity-inducing brain stimulation prior to the training than without preconditioning. Recently, a study with Parkinson’s disease patients also demonstrated that the outcomes of motor learning were more significant and sustainable after preconditioning with rTMS compared to without preconditioning [ 88 ].…”
Section: Future Research Direction: Cross-modal Preconditioningmentioning
confidence: 99%
“…Indeed, Ziemann et al [ 87 ] found that better outcomes on a thumb abduction movement training could be achieved when participants have received LTD-like plasticity-inducing brain stimulation prior to the training than without preconditioning. Recently, a study with Parkinson’s disease patients also demonstrated that the outcomes of motor learning were more significant and sustainable after preconditioning with rTMS compared to without preconditioning [ 88 ].…”
Section: Future Research Direction: Cross-modal Preconditioningmentioning
confidence: 99%
“…Finally, 32 articles were included according to the pre-determined inclusion criteria (Figure 1) (Table 1 and Table 2). 10-43…”
Section: Resultsmentioning
confidence: 99%
“…The distinct results can be due to the difference in the included trials and data extraction, as several positive-result studies published in recent years. 15,23,33,43 The novel dTMS was also included in the analysis, and the result showed a significant motor function improvement, which can be attributed to the deep and wide stimulation area. Besides, consistent with the previous reports, we found multiple-session is the better choice for the long-term benefit and more permanent changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged stimulation or combined targets 63 might be more efficacious but need to be further explored. Another promising approach is the use of TMS prior to a training intervention (e.g., prior to physiotherapy or treadmill) 66 . In these cases, the rationale is to strength the effectiveness of synaptic connections and recruit fibers required to improve performance during a given task such as gait 67 .…”
Section: Targeting Higher-order Posture-gait Structuresmentioning
confidence: 99%